Management of Innovation Factors of Sustainable Socially Oriented Economic Development: Generalizing Scientific Theories - Bondar-Pidhurska, O. (Економічний вісник Донбасу, 2019)
Scientific theories are generalized in the context of managing innovative factors of sustainable socially oriented economic development. Concepts of scientific theories aimed at ensuring sustainable innovative socially-oriented economic development (noospheric, neo-Keynesian, neo-Marxist, conflict, crisis and cyclical theories, economic evolutionary theories, including innovative ones; economics of behavior and inequality, social stratification; technical and technological structures; equivalence of material and spiritual factors of social development, «New theory of growth»), as well as tools for managing them to solve complex problems related to increasing the dynamics of challenges and threats (cybernetic control theory: theory of optimal control in economics and theory of automatic control)), have been analyzed and synthesized.
Scientific and technological progress (innovative development) as a factor of satisfaction of vital interests of the population and qualitative composition of the power elites (national establishment) as a driving force of economic development from the point of view of decision-making, concept development, strategy and its models were substantiated as a result.
The importance of preventing and overcoming negative phenomena by timely introduction of innovations into industry is emphasized, which will lead to intensive increase of labor productivity and growth of economic dynamics, which, in turn, will ensure the satisfaction of the majority population country vital interests.
The reasons and factors of inequality, elimination and timely management which will help to optimize the structure of country population stratification are revealed. Узагальнено наукові теорії у контексті управління інноваційними факторами сталого соціально орієнтованого розвитку економіки. Проаналізовано та синтезовано концепції наукових теорій спрямованих на забезпечення сталого інноваційного соціально орієнтованого розвитку економіки (ноосферна, неокейнсіанська, неомарксистська, конфліктності, теорії криз і циклічності, економічні еволюційні теорії, зокрема інноваційні; поведінкові економіки та нерівності, соціальної стратифікації; техніко-технологічних укладів; рівнозначності матеріальних і духовних чинників у суспільному розвитку, «Нова теорія зростання»), а також інструменти управління ним, які дозволяють розв’язувати складні проблеми, пов’язані із підвищенням динамізму викликів і загроз (кібернетична теорія управління: теорія оптимального управління в економіці та теорія автоматичного регулювання). У результаті обґрунтовано науково-технічний прогрес (інноваційний розвиток) як фактор задоволення життєво важливих інтересів населення, а якісний склад владних еліт (національного істеблішменту) як рушійні сили економічного розвитку у частині прийняття управлінських рішень, розробки концепцій, стратегій і його моделей.
Виявлено причини та чинники нерівності, усунення та вчасне управління якими допоможе оптимізувати структуру стратифікації населення.
Наголошено на доцільності упередження та подо¬лання негативних явищ за рахунок вчасного впровадження нововведень у промисловість, що спричинить інтенсивне підвищення продуктивності праці та зростання економічної динаміки, яка, в свою чергу, забезпечить задоволення життєво важливих інтересів більшості населення країни. Обобщены научные теории в контексте управления инновационными факторами устойчивого социально ориентированного развития экономики. Проанализированы и синтезированы концепции научных теорий направленных на обеспечение устойчивого инновационного социально ориентированного развития экономики (ноосферная, неокейнсианская, неомарксистская, конфликтности, теории кризисов и цикличности, экономические эволюционные теории, в частности инновационные; поведенческой экономики и неравенства, социальной стратификации; технико-технологических укладов; равнозначности материальных и духовных факторов в общественном развитии, «Новая теория роста»), а также инструменты управления им, которые позволяют решать сложные проблемы, связанные с повышением динамизма вызовов и угроз (кибернетическая теория управления: теория оптимального управления в экономике и теория автоматического регулирования). В результате обоснованы научно-технический прогресс (инновационное развитие) как фактор удовлетворения жизненно важных интересов населения, а качественный состав властных элит (национального истеблишмента) как движущие силы экономического развития в части принятия управленческих решений, разработки концепций, стратегий и его моделей.
Выявлены причины и факторы неравенства, устранение и своевременное управление которыми поможет оптимизировать структуру стратификации населения.
Отмечена целесообразность предупреждения и ликвидации негативных явлений за счет своевременной реализации нововведений в промышленность, что повлечет интенсивное повышение производительности труда и роста экономической динамики, которая, в свою очередь, обеспечит удовлетворение жизненно важных интересов большинства населения страны.